Pulmonary Arterial Pressure Changes Under Dobutamine Stress Echocardiography in Non-Anemic Iron Deficient COPD Subjects - Wanderley Xavier, Ana Christina; Koch, Rodrigo; Steinhorst Goelzer, Leandro; Muller, Paulo T (International journal of chronic obstructive pulmonary disease, 2022)
Purpose: Non-anemic iron deficiency (NAID) is common in COPD, and could induce functional/structural changes in the pulmonary vascular bed. Thus, we aimed to study, during resting and ambient oxygen conditions, the systolic pulmonary arterial pressure (sPAP) changes during dobutamine stress echocardiography (DSE) for NAID+ compared to NAID- subjects with COPD. Patients and Methods: We analyzed 24 patients with COPD and evaluated their clinical parameters, including lung function and serum iron profile, followed by the changes in the sPAP under DSE. Results: Ten subjects with NAID+ were compared with fourteen NAID- subjects for sPAP measurement. At baseline, only left atrial volume was significantly different between groups (30 [+ or -] 4 vs 23 [+ or -] 5 mL*m2), respectively (p-value=0.002). For the right side, tricuspid annular plane systolic excursion (TAPSE) was similar between-groups (22 [+ or -] 2 vs 20 [+ or -] 4, p-value >0.05), at baseline. The sPAP (mmHg) changes were also not significantly different between groups (pre 32 [+ or -] 14 vs peak 48 [+ or -] 14 for NAID+ and pre 29 [+ or -] 7 vs peak 43 [+ or -] 10 for NAID-, Group p-value=0.400, Time p-value <0.0001, and Interaction p-value=0.606). Conclusion: COPD subjects with NAID do not show increased sPAP responses during DSE, compared with iron-replete subjects. Keywords: COPD, iron deficiency, pulmonary hypertension, stress echocardiography